Electroless plating of copper nanoparticles on PET fiber for non-enzymatic electrochemical detection of H2O21. Issue 94 (14th October 2015) - Kim, Eunju; Sabari Arul, Narayanasamy; Yang, Liu; Han, Jeong In
<x xml:space="preserve">Abstract</x> We have fabricated copper nanoparticles (Cu NPs) on polyethylene terephthalate (PET) fiber by electroless plating for the electrochemical detection of hydrogen peroxide (H2O2) with an excellent sensitivity of 0.387 mA μM−1 cm−2.